Molecular Docking Studies for the Identification of Mycobacterial Adenosine Triphosphate (ATP) Synthase Inhibitors Using Active Phytocompounds from Plants Curcuma longa, Curcuma zedoaria and Galipea officinalis - Priyanka Raja; Shubham Wanarase (International Journal of Bioinformatics and Computational Biology, 2024)
Objective: Tuberculosis (TB), known in human history for several decades, remains the second leading infectious disease after COVID-19. Still, the occurrence of TB increases due to the bacterium’s greater survival nature. They can survive in extreme conditions by being in long latency and adapting to the host. This study seeks to identify potential inhibitors from Curcuma longa, Curcuma zeodaria, and Galipea officinalis based on ancient folklore and compare them against the known mycobacterial ATP-synthase inhibitor, bedaquiline. To perform docking studies, drug-likeness, and ADMET analysis. Methods: The structure of mycobacterial ATP-synthase was retrieved from the PDB database. Preparation of protein and docking studies were performed using the PyRx tool for the drug-likeliness study, the SwissADME webserver was used. For ADMET analysis, the ADMETlab webserver was used. Results: The docking study showed potential compounds that inhibit mycobacterial ATP-synthase thereby interfering with ATP synthesis besides the known inhibitor, bedaquiline. Among these six compounds, cyclocurcumin, cusparine, and galipeine had shown a similar binding nature compared to that of bedaquiline. The known inhibitor, bedaquiline inhibits the protein by blocking the rotation of the C chain which is the catalytic headpiece. Thus, it primarily inhibits the F-ATP synthesis in the bacterium. Conclusion: Considering the drug-likeliness and ADMET analysis, galipeine shows better safety and toxicity profile than Cyclocurcumin. The study proposes Cyclocurcumin and galipeine as potential inhibitors of mycobacterial ATP-synthase for designing a therapeutic compound, by exploiting the phytocompounds especially known for their purpose for treating tuberculosis based on ancient folklore.
Keywords: Galipea officinalis, traditional medicine; Tuberculosis, mycobacterial ATP-synthase, Curcuma longa, Curcuma zeodaria